Lack of Influence of Serum Magnesium Levels on Overall Mortality and Cardiovascular Outcomes in Patients with Advanced Chronic Kidney Disease. (19th June 2013) - Ortega, Olimpia; Rodriguez, Isabel; Cobo, Gabriela; Hinostroza, Julie; Gallar, Paloma; Mon, Carmen; Ortiz, Milagros; Herrero, Juan Carlos; Di Gioia, Cristina; Oliet, Aniana; Vigil, Ana
Abstract : Background . Low serum magnesium has been associated with an increased cardiovascular risk in the general population and in dialysis patients. Our aim was to analyze the influence of serum magnesium on overall mortality and cardiovascular outcomes in patients with advanced CKD not yet on dialysis. Methods . Seventy patients with CKD stages 4 and 5 were included. After a single measurement of s-magnesium, patients were followed a mean of 11 months. Primary end-point was death of any cause, and secondary end-point was the occurrence of fatal or nonfatal CV events. Results . Basal s-magnesium was within normal range (2.1 ± 0.3  mg/dL), was lower in men( P = 0.008 ) and in diabetic patients( P = 0.02 ), and was not different( P = 0.2 ) between patients with and without cardiopathy. Magnesium did not correlate with PTH, calcium, phosphate, albumin, inflammatory parameters (CRP), and cardiac (NT-proBNP) biomarkers but correlated inversely( r = − 0.23 ;P = 0.052 ) with the daily dose of loop diuretics. In univariate and multivariate Cox proportional hazard models, magnesium was not an independent predictor for overall mortality or CV events. Conclusions . Our results do not support that serum magnesium can be an independent predictor for overall mortality or future cardiovascular events among patients with advanced CKD not yet on dialysis.